Does Consumer Confidence Forecast Consumption Expenditure in New Zealand? - Khoon Lek Goh (New Zealand Government, The Treasury, 2003)
This paper examines the ability of consumer confidence to forecast consumption expenditure in New Zealand. A two-step process commonly used by other researchers, which was developed by Carroll, Fuhrer and Wilcox (1994), was utilised. The two most widely followed and reported measures of consumer confidence in New Zealand – the One News Colmar Brunton Poll and the Westpac McDermott Miller Consumer Confidence Survey – were used. Lagged values of consumer confidence on its own were found to have some predictive ability for forecasting consumption growth. However, this predictive ability was greatly reduced when control variables – labour income, interest rates and stock prices - were introduced, suggesting that consumer confidence merely reflects current economic conditions. Because of this, consumer confidence provides little additional information above readily available economic and financial data for forecasting consumption. However, since confidence indexes are available in a timely manner compared to economic data, they still provide useful summary information for making assessments of current economic conditions.
Keywords: E21; E27; 330; Consumer confidence; consumption; forecasting